Optimalisasi Partisipasi Anggota Koperasi Mahasiswa Melalui Digitalisasi Layanan Serta Potensi Pengembangan Bisnisnya - Muhammad Syaiful; Sapriyadi, Sapriyadi; Syakila, Syakila (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The demand to transform conventional systems into ones that utilize digital platforms is inevitable. Digital transformation is crucial, especially in the customer service sector, to facilitate transactions for consumers. The opportunity to undertake digital transformation within cooperatives is wide open due to the rapid technological advancements today. The specific objective of this research is to understand how the digitalization of services conducted by student cooperatives contributes to enhancing member participation, and also to identify the potential for the development of student cooperative businesses. This research is conducted at the Student Cooperative of Economics Education in Kendari City, Southeast Sulawesi. Informants for this study consist of cooperative advisors, management members, cooperative members, and alumni who were members of the cooperative. Data collection for this research was obtained through three methods: observation of the research location, interviews with the informants, and literature review. Data reduction, data presentation, and drawing conclusions are the methods used to analyze the qualitative data obtained from interview results. The research findings reveal that the student cooperative management has taken initiatives to optimize member participation, such as developing the "KopmaKu" application, attempting collaboration with third-party cooperative application developers, and working towards implementing Quick Response Code Indonesian Standard (QRIS) as a payment system. Student cooperative business units have significant potential to provide benefits and opportunities for alumni. These cooperatives serve not only as places for purchasing essential items, but also as platforms for collaboration, empowerment, and connections between students and alumni. The student cooperative business units can serve as a strong bridge between students and alumni. Alumni can collaborate with students in various aspects, including the provision of products or services, training, and even funding.